Short‐Term Exposure to Air Pollution and Biomarkers of Oxidative Stress: The Framingham Heart Study - Li, Wenyuan (J Am Heart Assoc, 2016)
BACKGROUND: Short‐term exposure to elevated air pollution has been associated with higher risk of acute cardiovascular diseases, with systemic oxidative stress induced by air pollution hypothesized as an important underlying mechanism. However, few community‐based studies have assessed this association. METHODS AND RESULTS: Two thousand thirty‐five Framingham Offspring Cohort participants living within 50 km of the Harvard Boston Supersite who were not current smokers were included. We assessed circulating biomarkers of oxidative stress including blood myeloperoxidase at the seventh examination (1998–2001) and urinary creatinine‐indexed 8‐epi‐prostaglandin F(2α) (8‐epi‐PGF (2α)) at the seventh and eighth (2005–2008) examinations. We measured fine particulate matter (PM (2.5)), black carbon, sulfate, nitrogen oxides, and ozone at the Supersite and calculated 1‐, 2‐, 3‐, 5‐, and 7‐day moving averages of each pollutant. Measured myeloperoxidase and 8‐epi‐PGF (2α) were log(e) transformed. We used linear regression models and linear mixed‐effects models with random intercepts for myeloperoxidase and indexed 8‐epi‐PGF (2α), respectively. Models were adjusted for demographic variables, individual‐ and area‐level measures of socioeconomic position, clinical and lifestyle factors, weather, and temporal trend. We found positive associations of PM (2.5) and black carbon with myeloperoxidase across multiple moving averages. Additionally, 2‐ to 7‐day moving averages of PM (2.5) and sulfate were consistently positively associated with 8‐epi‐PGF (2α). Stronger positive associations of black carbon and sulfate with myeloperoxidase were observed among participants with diabetes than in those without. CONCLUSIONS: Our community‐based investigation supports an association of select markers of ambient air pollution with circulating biomarkers of oxidative stress.